The adaptation of Acidithiobacillus Ferrooxidans to tolerate higher concentrations of CU and NI - 250265 Lai, Huat Choi (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2004